Size, Leverage dan Profitabilitas Terhadap Audit Delay yang Berdampak pada Earning Response Coefficient Perusahaan Perdagangan Besar di Bursa Efek Indonesia - Astuti Astuti; Christine Dewi Nainggolan; Lenny Dermawan Sembiring (Jurnal Akuntansi dan Pajak, 2023)
Financial information is said to be relevant if it has a predicted value, a feedback value, and is timely. Audit delay will cause the resulting information to be less useful for users and can increase uncertainty for investors in making investment decisions. This research aims to analyze the effect of size, leverage and profitability on audit delay, the effect of size, leverage, profitability and audit delay on the earnings response coefficient as well as the effect of size, leverage and profitability on the earnings response coefficient through audit delay. The research was conducted on 13 Large Trading Companies during the period 2017-2021 that have met the sampling criteria. The analysis method uses classical assumption tests, coefficient of determination tests (R square) and hypothesis testing including simultaneous significance test (F test), partial significance test (t test) and sobel test analysis. The results showed that size and leverage had an effect on audit delay, profitability did not affect audit delay, and size, leverage, profitability and audit delay did not affect ERC. From the results of the sobel test, it shows that the audit delay does not have an impact on the ERC.